Analisis Faktor-faktor yang Mempengaruhi Kinerja Perusahaan Sekuritas Anggota Dana Perlindungan Pemodal - Bayu Priguna (The Indonesia Capital Market Institute, 2019)
This research discusses the factors that influence the performance of the securities firms in Indonesia. Based on the theory of structure, conduct, and performance (SCP), the firm's performance, measured by profitability, will be influenced by market concentration (traditional hypothesis), market share (differentiation hypothesis), efficiency (efficiency structure hypothesis). Another theory stated that macroeconomic variables such as interest rate can affect firm’s performance. This thesis uses panel data regression with Estimated Generalized Least Square (EGLS) method with random effect which statistically shows that efficiency, interest rate, and market share affect profitability of securities firms. While other variable representing market concentration, concentration ratio does not affect profitability.